Effects of digitalization on business models and sustainability of the fishing industry - Zanfrillo, Alicia Inés (2024)
Purpose: Describe the development of digital business models of fishing companies in the city of Mar del Plata and their relationship with the sustainability of production processes. Methodology: The research is based on a descriptive-correlational quantitative methodology, with the application of a multivariate analysis technique, cluster analysis, to identify groupings of companies based on secondary sources of information. Results: Mar del Plata fishing companies offer different asymmetries in the development of their business model through digital marketing channels, with few representations of current technological advances in the final stretch of the value chain. Research limitations: The limitation of the work lies in the lack of longitudinal data that prevents evaluating long-term changes in the integration of digitalization and sustainability. Originality: The study on business models and environmental commitment in the fishing industry in the southeast of the province of Buenos Aires reveals a predominant emphasis on commercial innovation, often to the detriment of comprehensive approaches. This approach decouples digitalization from sustainability, particularly among the sector's pioneers.